Insect Cells for High-Yield Production of SARS-CoV-2 Spike Protein: Building a Virosome-Based COVID-19 Vaccine Candidate - Bárbara Fernandes; Rute Castro; Farien Bhoelan; Denzel Bemelman; Ricardo A. Gomes; Júlia Costa; Patrícia Gomes-Alves; Toon Stegmann; Mario Amacker; Paula M. Alves; Sylvain Fleury; António Roldão (MDPI AG, 2022)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) homotrimeric spike (S) protein is responsible for mediating host cell entry by binding to the angiotensin-converting enzyme 2 (ACE2) receptor, thus being a key viral antigen to target in a coronavirus disease 19 (COVID-19) vaccine. Despite the availability of COVID-19 vaccines, low vaccine coverage as well as unvaccinated and immune compromised subjects are contributing to the emergence of SARS-CoV-2 variants of concern. Therefore, continued development of novel and/or updated vaccines is essential for protecting against such new variants. In this study, we developed a scalable bioprocess using the insect cells-baculovirus expression vector system (IC-BEVS) to produce high-quality S protein, stabilized in its pre-fusion conformation, for inclusion in a virosome-based COVID-19 vaccine candidate. By exploring different bioprocess engineering strategies (i.e., signal peptides, baculovirus transfer vectors, cell lines, infection strategies and formulation buffers), we were able to obtain ~4 mg/L of purified S protein, which, to the best of our knowledge, is the highest value achieved to date using insect cells. In addition, the insect cell-derived S protein exhibited glycan processing similar to mammalian cells and mid-term stability upon storage (up to 90 days at −80 and 4 °C or after 5 freeze-thaw cycles). Noteworthy, antigenicity of S protein, either as single antigen or displayed on the surface of virosomes, was confirmed by ELISA, with binding of ACE2 receptor, pan-SARS antibody CR3022 and neutralizing antibodies to the various epitope clusters on the S protein. Binding capacity was also maintained on virosomes-S stored at 4 °C for 1 month. This work demonstrates the potential of using IC-BEVS to produce the highly glycosylated and complex S protein, without compromising its integrity and antigenicity, to be included in a virosome-based COVID-19 vaccine candidate.